2017
DOI: 10.1002/ece3.3503
|View full text |Cite
|
Sign up to set email alerts
|

Radiation of the polymorphic Little Devil poison frog (Oophaga sylvatica) in Ecuador

Abstract: Some South American poison frogs (Dendrobatidae) are chemically defended and use bright aposematic colors to warn potential predators of their unpalatability. Aposematic signals are often frequency‐dependent where individuals deviating from a local model are at a higher risk of predation. However, extreme diversity in the aposematic signal has been documented in poison frogs, especially in Oophaga. Here, we explore the phylogeographic pattern among color‐divergent populations of the Little Devil poison frog Oo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 68 publications
2
23
0
Order By: Relevance
“…Our results demonstrate that characterization of morphs based solely on observed phenotypic variation, especially when genetic structure is unresolved, can lead to an overestimation of the degree of polymorphism and/or polytypism that occurs in aposematic systems. Our findings are consistent with other studies in Neotropical poison frogs where sophisticated genetic datasets, utilized either in isolation or paired with morphological and ecological data, have revealed that a single species likely includes several distinct lineages (Posso‐Terranova & Andrés, ; Roland et al, ). Thus, overestimation of intraspecific variation and underestimation of species diversity in phenotypically diverse lineages may be more widespread than previously appreciated.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results demonstrate that characterization of morphs based solely on observed phenotypic variation, especially when genetic structure is unresolved, can lead to an overestimation of the degree of polymorphism and/or polytypism that occurs in aposematic systems. Our findings are consistent with other studies in Neotropical poison frogs where sophisticated genetic datasets, utilized either in isolation or paired with morphological and ecological data, have revealed that a single species likely includes several distinct lineages (Posso‐Terranova & Andrés, ; Roland et al, ). Thus, overestimation of intraspecific variation and underestimation of species diversity in phenotypically diverse lineages may be more widespread than previously appreciated.…”
Section: Discussionsupporting
confidence: 92%
“…In systems with high color variability, however, determining whether color variants represent different species, different populations, or different morphs within populations is difficult particularly when genetic structure is not well resolved. Distinguishing between species, populations, and morphs can be especially challenging in phenotypically diverse poison frog groups, where high rates of phenotypic variation can confound our understanding of species delimitations (Posso‐Terranova & Andrés, ; Roland et al, ; Tarvin, Powell, Santos, Ron, & Cannatella, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little devil (or diablito) frogs [Oophaga sylvatica (Funkhouser 1956) N=13] were collected during the day near the Otokiki Reserve (GPS coordinates: latitude 0.91075, longitude −78.57555, altitude 704 m) maintained by WIKIRI/Fundación Otonga in northwestern Ecuador in July 2013 (Roland et al, 2017). Frogs were individually stored in plastic bags with air and vegetation for 2-5 h. In the evening the same day of capture, adult frogs (over 1 yr of age; five females and three males) were anesthetized with a topical application of 20% benzocaine to the ventral belly and euthanized by cervical transection.…”
Section: Materials and Methods Field Collection Of Oophaga Sylvaticamentioning
confidence: 99%
“…Little Devil (or Diablito) frogs [Oophaga sylvatica, (Funkhouser) N=13] were collected during the day near the Otokiki Reserve (GPS coordinate: latitude 0.91075, longitude -78.57555, altitude 704m) maintained by WIKIRI/Fundación Otonga in northwestern Ecuador in July 2013 (Roland et al, 2017). Frogs were individually stored in plastic bags with air and vegetation for 2-5 hours.…”
Section: Field Collection Of Oophaga Sylvaticamentioning
confidence: 99%